The Trust And Acceptance Of Internet Banking Of The Customers Of The Municipal Savings And Credit Bank Of Lambayeque (Journal of Namibian Studies : History Politics Culture, 2023)
In this digital era, in which financial institutions have been forced to use various platforms in order to improve the customer experience and service, this research work was proposed, which had the objective of evaluating the existence of a relationship between trust and the acceptance of internet banking for the clients of the Lambayeque municipal savings and credit banks. For this, a quantitative approach was used, of a correlational level and a non-experimental, cross-sectional design in which a sample of 179 clients of the entities under study was studied. The questionnaire was used as an instrument to collect information from the sample through the survey technique. The findings showed the presence of a direct relationship between trust in the financial institution and the acceptance of internet banking services in the clients of the Lambayeque municipal savings and credit banks, however, this relationship was not fulfilled in the attitude toward use and behavioral intention to use internet banking.